PENINGKATAN KETERAMPILAN BERPIKIR KREATIF PESERTA DIDIK KELAS 2 MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING - Dian Kartikasari; Meirza Nanda Faradita; Iswahyuni (Universitas Muhammadiyah Surabaya, 2024)
The research about the increasing’s creative thinking skills of class 2 students through the Project Based Learning learning model has been done. The purposed of the research were to finished learning outcomes and creative thinking skills of students using the Project Based Learning learning model on time material in class II-B SD Khadijah Surabaya. This research is classroom action research (PTK) with two cycles, each cycle consisting of preparation/planning, implementation/execution of activities, observation and reflection. The targets in this research were class II-B students at SD Khadijah Surabaya for the 2023-2024 academic year, totaling 32 students. The learning tools consist of teaching modules, LKPD, teaching materials, while the instruments used are knowledge assessment sheets and observation sheets for students' creative thinking skills. Based on the research results, it was found that students' learning outcomes and creative thinking skills had increased with an average for cycle I of 68. 75 and cycle II of 87. 5 with classical completeness meeting expectations, namely reaching ≥ 85%. From the research results, it can be concluded that students' learning outcomes and creative thinking skills in time material can be improved through the Project Based Learning learning model.